MODEL ASESMEN ALTERNATIF DALAM EVALUASI PEMBELAJARAN DI ERA PANDEMI COVID-19 - Sri Hastuti; Ismail Marzuki (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2021)
Learning activities during the Covid-19 pandemic have changed the paradigm of education and require all parties to change the learning system using online media. This includes assessment activities for students. Therefore it is necessary to have an alternative assessment model that supports a good and effective online learning process, both for educators and students. This study seeks to provide an overview of alternative forms of assessment and evaluation that can be used as a model for educators in assessing and evaluating student learning outcomes during the Covid-19 pandemic that hit Indonesia. This research is a type of qualitative research. Researchers obtained data from the results of literature studies from various books, journals, scientific papers, and also other documents that examine assessment and evaluation of learning, both in general and specifically examining the assessment and evaluation of online learning. The results of this study are several forms of assessment models that can be applied in the online learning process, including online-based assessment, portfolio assessment, and character assessment.